2012
DOI: 10.1186/cc11847
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 is a novel candidate diagnostic biomarker for bacterial infection in critically ill children

Abstract: IntroductionDifferentiating between sterile inflammation and bacterial infection in critically ill patients with fever and other signs of the systemic inflammatory response syndrome (SIRS) remains a clinical challenge. The objective of our study was to mine an existing genome-wide expression database for the discovery of candidate diagnostic biomarkers to predict the presence of bacterial infection in critically ill children.MethodsGenome-wide expression data were compared between patients with SIRS having neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 29 publications
4
99
2
Order By: Relevance
“…In a recent study, EBI3 was found to be highly expressed in the blood of patients with systemic inflammatory response syndrome, and therefore it was proposed to be a candidate diagnostic biomarker for bacterial infection (Wong et al, 2012). In our study, qRT-PCR analysis showed that under normal physiological conditions, CsE-BI3 expression was most abundant in immune tissues and upregulated in kidney and spleen by E. tarda and megalocytivirus challenge.…”
Section: Discussionmentioning
confidence: 50%
“…In a recent study, EBI3 was found to be highly expressed in the blood of patients with systemic inflammatory response syndrome, and therefore it was proposed to be a candidate diagnostic biomarker for bacterial infection (Wong et al, 2012). In our study, qRT-PCR analysis showed that under normal physiological conditions, CsE-BI3 expression was most abundant in immune tissues and upregulated in kidney and spleen by E. tarda and megalocytivirus challenge.…”
Section: Discussionmentioning
confidence: 50%
“…Multiple reports have shown basal levels of circulating IL-27p28 in humans; these levels are altered in many disease states, including bacterial infections, sepsis, aplastic anemia, and ankylosing spondylitis (167)(168)(169)(170)(171). The interpretation of what the changes in levels of IL-27 mean is not straightforward; increased production could indicate causality or simply be a secondary host response to ongoing disease.…”
Section: Translational Implications Of Il-27mentioning
confidence: 94%
“…Arkader et al (10) compared 14 patients who were post-cardiopulmonary bypass (CPB) (to emulate SIRS patients) and patients with confirmed bacterial sepsis and concluded that PCT had 83% sensitivity and 93% specificity when using a cutoff of 1.0 ng/mL. Wong et al (11) showed an elevation in PCT in patients with septic shock as compared with patients with SIRS or sepsis. Both of these studies used patients with SIRS as control patients and patients with sepsis as study patients.…”
Section: Secondary Analysesmentioning
confidence: 96%